Thirty years of clear-cutting maintain diversity and functional composition of woody-encroached Neotropical savannas - Giles, André L. [UNESP]; Flores, Bernardo M.; Rezende, Andréia Alves [UNESP]; Weiser, Veridiana de Lara [UNESP]; Cavassan, Osmar [UNESP] (Elsevier, 2021)
Humans have changed vegetation dynamics in Neotropical savannas by suppressing fires, allowing trees and shrubs to expand into ancient savanna landscapes in a process known as woody encroachment. This woody encroachment drives the loss of biodiversity and modifies the functioning of savanna ecosystems. Here we combine satellite data analysis with an experimental approach to test the hypothesis that long-term management by clear-cutting helps restore the diversity and functional composition of open savannas. First, we used Landsat time series of the Normalized Difference Water Index, to assess changes in vegetation structure, comparing experimental areas with open savannas in the same region. We then obtained field experimental evidence comparing areas managed during 30 years versus unmanaged areas, including data on vegetation structure and composition. Our results from satellite image analyses indicate that, before the first clear-cutting, vegetation structure was similar in managed and unmanaged sites, and both differed from open savanna. When clear-cutting manipulation started, NDWI of managed areas became persistently lower than that of unmanaged control areas. In the field, we found that in managed areas, species diversity and richness of typical savanna species had increased, and that species composition had changed to become more similar to open savannas. We also observed the recovery of savanna functional composition, suggesting that ecosystem processes were restored by clear-cutting management. Our findings reveal that the repeated removal of dominant woody species by clear-cutting has contributed to maintain the diversity and functioning of savannas degraded by forest encroachment.
Keywords: Cerrado; Community structure; Disturbance; Floristic composition; Management; Vegetation change